Immersive Virtual Reality Improves Vocational Students’ Industry-Based Building Material Design Skills - Galeh Nur Indriatno Putra Pratama; Mochammad Bruri Triyono; Candra Dinata; Thomas Koehler; Mario Gandra; Basanta Prasad Adhikari; Dias Aziz Pramudita (Jurnal VARIDIKA, 2027)
The rapid advancement of immersive technology has reshaped vocational education, emphasizing the need for effective learning strategies to enhance industry-based design skills. Virtual Reality (VR) offers an immersive, interactive environment that bridges academic learning and industry requirements. This study aims to the effectiveness of VR simulation media in building construction for improving design skills. A quasi-experimental pretest–posttest design was used involving 84 students from the Civil Engineering and Planning Education Study Program, Yogyakarta State University, divided into experimental and control groups of 42 students each. Data were collected through observation, tests, and portfolio assessments based on VR simulation activities, and analyzed using a t-test. The results show that the use of VR-based building construction simulation media in construction design courses was effective in enhancing students’ design competencies, which was confirmed by the t-test analysis results (sig. < 0.05). Students’ design abilities were further developed through various design experiments carried out using the VR simulation outputs.